If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(y) = cos(2y) Multiply f * y fy = cos(2y) Remove parenthesis around (2y) fy = cos * 2y Reorder the terms for easier multiplication: fy = 2cos * y Multiply cos * y fy = 2cosy Solving fy = 2cosy Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'y'. f = 2cos Simplifying f = 2cos
| -3x+6(5x-2)=-6 | | hot+girl= | | 8(x-2)=5x+11+3x | | 3x+3(x+15)=15 | | 4n=0.56 | | x^2y-9y+3x-27=0 | | 5(x+-4)+2x=14 | | y=4(1.666666667)+6 | | 5x-15=20-2x | | 10cos(x)+sin^2(x)=0 | | mx+nc=y | | 2x^4-8=0 | | 2x^5-8=0 | | (-25)x(-13)= | | -25x-13= | | 8.3(x-31)=-37.35 | | 2z^2+7z+5=6z^2 | | (logx)6561=8 | | 9x+18=5x+38 | | x+4(-1)=8 | | 7x-4(-2x+7)=-193 | | X+7=3(x+7)-19 | | R=176-0.8x | | -4+(-2)x-3= | | 14m-32=22 | | 15x^2-165x+630=0 | | x+2+x+2+x+2=36 | | X^2=1966 | | -16x^2+150x-3=0 | | 5x^2-12=-8x | | 8(x+7)+6=8.6x-6 | | 5w^2-60=0 |